Economic analysis of dairy cattle farms in east Mediterranean region of Turkey - Yilmaz,Hilal (2016)
ABSTRACT The purpose of this study was to calculate costs of milk production, gross production value, gross margin, absolute profit, and relative profit of dairy cattle farms located in the provinces of east Mediterranean region of Turkey. Primary data were collected from 148 dairy cattle farms designated using the Neyman Stratified Sampling method through surveys. Dairy farms were classified into four groups according to the number of cows. The data belong to the 2012 production season. A single product budget analysis method was used for calculating production costs. According to the results, variable costs amounted to 65.91% of total production costs. Feed cost (86.52%) was the main component of variable costs. The cost of 1 kg of milk, on average, was calculated as USD 0.261. The cost of milk was USD 0.499 on group 1 farms, USD 0.399 on group 2 farms, USD 0.272 on group 3 farms, and USD 0.233 on group 4 farms. Among the farms under study, average gross margin value was negative only on group 1 farm, and positive in all other groups. Absolute profit value was positive only on group 4 farm, and negative in all other groups. The average relative profit of the farms was 0.9067. The expansion of dairy farms could be reached by reducing the feed cost as well as increasing the scale of farms.